Golf ball - Brown, Harry J. (Harry John), 1972- (Bloomsbury Academic, 2015)
Object Lessons is a series of short, beautifully designed books about the hidden lives of ordinary things. Harry Brown explores the composition, history, kinetic life, and the long deterioration of golf balls, which as it turns out may outlive their hitters by a thousand years, in places far beyond our reach. Golf balls embody our efforts to impose our will on the land, whether the local golf course or the Moon, but their unpredictable spin, bounce, and roll often defy our control. Despite their considerable technical refinements, golf balls reveal the futility of control. They inevita.